The association between the cystatin C- and creatinine-based estimated GFR ratio and post-ablation outcomes in patients with atrial fibrillation - Wenchao Huang; Luxiang Shang; Yan Luo; Shiqiang Xiong; Shuwei Suo; Zhen Zhang; Hanxiong Liu; Huaxin Sun (Renal Failure)
Background The difference between the cystatin C-based eGFR (eGFRcys) and the creatinine-based eGFR (eGFRcr) is associated with the risk of developing atrial fibrillation (AF) risk. However, its impact on AF ablation outcomes is unknown.Methods The associations between the baseline eGFR ratio (eGFRcys/eGFRcr) and the risk of experiencing post-ablation endpoints were evaluated on a continuous scale (restricted cubic splines) and by a priori defined centile categories with Cox proportional hazards regression models. The primary endpoints were AF recurrence and adverse events; the secondary endpoint was rehospitalization.Results Among 989 participants (49.2% women; mean age 65.7 years), 313 experienced AF recurrence after a median follow-up of 28 months. After full adjustment for confounding factors, a U-shaped association was observed between eGFR ratio and AF recurrence risk (minimum risk at 0.797). Although a U-shaped trend was observed, there was no statistically significant association between the eGFR ratio and adverse events or rehospitalization. Hazard ratios for AF recurrence, compared to the second quartile, were 1.68 (1.20–2.37) for the first quartile, 1.64 (1.15–2.34) for the third quartile, and 1.96 (1.37–2.80) for the fourth quartile. According to the subgroup analysis, the above association was strongly U-shaped for males and linear for females.Conclusion In the AF population, both low and high eGFR ratios were associated with an increased risk of post-ablation AF recurrence.